2006
DOI: 10.1111/j.1471-4159.2006.04352.x
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate induces histone H3 phosphorylation but not acetylation in striatal neurons: role of mitogen‐ and stress‐activated kinase‐1

Abstract: Chromatin remodelling is thought to play a key role in gene regulation that underlies long-term synaptic plasticity and memory formation. The dynamic process of chromatin remodelling requires post-translational modifications of histones, a group of highly basic proteins that are tightly linked to DNA. In the present study, we investigated histone H3 modifications in response to glutamate stimulation leading to c-Fos and c-Jun induction in an in vitro model system of striatal neurons in culture. Intracellular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 34 publications
3
63
0
Order By: Relevance
“…Earlier analyses on histone acetylation in response to cocaine (Brami-Cherrier et al, 2007, 2005Cassel et al, 2006) or ethanol (Kim and Shukla, 2006;Pandey et al, 2008) have produced somewhat conflicting results. Despite the dose-dependent hyperacetylation observed in response to sodium butyrate, our analysis failed to reveal significant changes in bulk chromatin acetylation after acute administration of cocaine, ethanol, or morphine to saline or sodium butyrate-pretreated mice.…”
Section: Discussionmentioning
confidence: 98%
“…Earlier analyses on histone acetylation in response to cocaine (Brami-Cherrier et al, 2007, 2005Cassel et al, 2006) or ethanol (Kim and Shukla, 2006;Pandey et al, 2008) have produced somewhat conflicting results. Despite the dose-dependent hyperacetylation observed in response to sodium butyrate, our analysis failed to reveal significant changes in bulk chromatin acetylation after acute administration of cocaine, ethanol, or morphine to saline or sodium butyrate-pretreated mice.…”
Section: Discussionmentioning
confidence: 98%
“…We observed that some important nuclear events driven by activated ERKs were not affected by the peptide, namely phosphorylation of MSK-1, CREB and histone H3. MSK-1 is a direct nuclear target of ERK with no DEF domain (Sharrocks et al, 2000), critically involved in both CREB and histone H3 phosphorylation in striatal neurons (Brami-Cherrier et al, 2005, 2007. As a consequence, the pattern of gene expression induced by glutamate was differently affected by the TAT-DEF-Elk-1 peptide compared with a classical MEK inhibitor, which had a more widespread effect.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, we chose IEGs that are controlled by the ERK cascade via their SRE and/or CRE binding domains (namely c-Fos, Zif268 and JunB) or via histone H3 phosphorylation (namely c-Jun) (supplemental Fig. 1, available at www.jneurosci.org as supplemental material) (Brami-Cherrier et al, 2007). The U0126 compound had a profound inhibitory role on glutamate-induced c-Fos, Zif268 and JunB induced expression (Fig.…”
Section: Comparative Effects Of Mek Inhibitor and Tat-def-elk-1 Peptimentioning
confidence: 99%
“…It is well known that mitogen-and stress-activated kinase 1 (MSK1), a kinase downstream of ERK, plays an important role in modification of histone H3 [23,24]. We examined whether MSK1 is phosphorylated during treatment with quercetin.…”
Section: Erk Mediates the Phosphorylation Of Msk1 By Quercetinmentioning
confidence: 99%